The Relationship Between Student Stress Level and Clinical Registration Outcomes in Students of The Faculty of Medicine Yarsi University Class Of 2016 and Views According to Islam - Rahmanita Fauziah; Miranti Pusparini; Endy Muhammad Astiwara (Junior Medical Journal, 2022)
Stress is a pattern of reaction and general adaptation, in the sense that the pattern of reaction to a stressor, which can come from within or outside the individual concerned, can be real or not real in nature. This study aims to determine the level of stress experienced by students of the Faculty of Medicine, Yarsi University class of 2016 and its relation to the results of the clerk's office. The research design used was cross sectional. Student stress levels were measured using the Perceived Stress Scale questionnaire. Data on clinical clerkship results were obtained from exam results. The results of the study were obtained from 85 students, 47.1% of Yarsi University Faculty of Medicine students class of 2016 experienced mild stress levels, 31.8% experienced moderate stress levels, and 21.2% experienced severe stress levels. This means that the stress level of Yarsi University Medical Faculty students is in the mild to moderate criteria. The results showed that the level of mild stress was higher in the number of students who got an A clerkship score, namely 3 out of 40 people (3.54) and 37 people (43.53%) got an A- clerkship score. Furthermore, students with high levels of stress got more AB scores, namely 12 students out of 18 students (14.12%). In this study, it was found that there was a relationship between stress levels and the results of clinical clerkship scores (p value 0.05).